Herzberg's theory and job satisfaction: A study of industrial SMEs in Morocco - Faiçal Abou Moudriq,; SOUDANE, Jalila AIT (Edelweiss Applied Science and Technology, 2025)
Employee job satisfaction is a significant factor in corporate performance and competitiveness today. This article examines the applicability of Herzberg's theory and what motivates employees in Moroccan industrial companies and their level of job satisfaction, using "hygiene" and "motivation" factors. To this end, the study was conducted on a sample of 200 employees divided into two socio-professional categories: administrative staff and blue-collar workers from three Moroccan industrial companies. Based on a multiple linear regression of responses collected via a live questionnaire, the analysis confirmed the applicability of Herzberg's theory. It showed that the factors determining job satisfaction among administrative staff differ from those of blue-collar workers. For blue-collar workers, salary and job security strongly impact job satisfaction, whereas for administrative staff, job satisfaction is determined more by job satisfaction and career development.